2022
DOI: 10.1002/alz.12910
|View full text |Cite
|
Sign up to set email alerts
|

Association of impaired kidney function with dementia and brain pathologies: A community‐based cohort study

Abstract: Introduction The relationship between impaired kidney function (KF), dementia, and brain pathologies remains unclear. Methods A total of 1354 dementia‐ and kidney disease‐free participants including 895 with normal and 459 with impaired KF were followed from 2002 until 2020 (median [interquartile range]: 5 [2–9]) to detect incident dementia. KF was assessed at baseline and categorized as normal or impaired. Over the follow‐up, 453 participants died and underwent autopsies for neuropathological assessment. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Second, the diagnoses recorded in the patient registry have high specificity but relatively low sensitivity (the positive predictive value of dementia cases is 80%–87% in the UK Biobank) ( 47 ), and this might also lead to the underestimation of the association between kidney function and dementia risk. However, the observed association in this study is comparable with that reported in our previous study, in which dementia was diagnosed based on yearly follow-up examinations by a physician (eGFR ≥ 60 vs <60; HR = 1.67, 95%CI: 1.14 to 2.44) ( 48 ). Therefore, the underestimation may not be substantial.…”
Section: Discussionsupporting
confidence: 90%
“…Second, the diagnoses recorded in the patient registry have high specificity but relatively low sensitivity (the positive predictive value of dementia cases is 80%–87% in the UK Biobank) ( 47 ), and this might also lead to the underestimation of the association between kidney function and dementia risk. However, the observed association in this study is comparable with that reported in our previous study, in which dementia was diagnosed based on yearly follow-up examinations by a physician (eGFR ≥ 60 vs <60; HR = 1.67, 95%CI: 1.14 to 2.44) ( 48 ). Therefore, the underestimation may not be substantial.…”
Section: Discussionsupporting
confidence: 90%
“…Autopsy and amyloid PET studies indicate that despite higher prevalence of cognitive impairment, patients with CKD do not have a higher prevalence of typical cerebral amyloid and tau pathology seen in AD. 10 , 39 , 40 CKD is however associated with cerebral amyloid angiopathy 40 which in theory could contribute to elevated Aβ levels in CKD. While it is common for patients with CKD to get diagnosed with AD, this diagnosis is generally made clinically without confirmation of the presence of cerebral amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have indicated that tau could be present in kidney, playing a role in the morphology of podocyte architecture [76]. Also, in some tauopathies, like frontotemporal dementia, some patients report urinary incontinence [77] and, more recently, the association of impaired kidney functions with dementia and brain pathologies has been indicated [78,79]. Curiously, AD patients with chronic kidney disease (CKD) treated with cholinesterase inhibitors showed a lower risk of CKD [80].…”
Section: Kidneymentioning
confidence: 99%